IMPLEMENTASI PERMAINAN FLOW PADA PEMBANGUNAN SISTEM CAPTCHA - Indra Setiawan; Willy Sudiarto Raharjo; Budi Susanto (Universitas Kristen Duta Wacana, 2016)
The basic challenge in designing an obfuscating CAPTCHAs is to make them easy enough that users are not dissuaded from attempting a solution, yet still too difficult to solve using available image-based computer vision algorithms. CAPTCHA has been widely used in many web applications and there has been so many research on CAPTCHA. Current technology enables computer to easily solve image-based CAPTCHA with high probability, so we propose another type of CAPTCHA-based authenticaton that can not be solved by utilizing Optical Character Recognition but still easy to use for new users. We implemented the new model of CAPTCHA using FLOW game. We found that the success rate of this new system is 92.025%, completion time is 6.3614s, and 81,67% of users are able to solve it in less than 10s.